Success and Failure at Dual-Task Coordination by Younger and Older Adults. - Hartley, Alan A.; Maquestiaux, François (Psychology & Aging, 2007)
Dual-task processing was explored in younger and older adults in 2 experiments that used a tone discrimination and a letter discrimination task. To encourage parallel processing if that was possible, the authors presented the stimuli for the 2 tasks simultaneously, and participants were instructed to withhold their responses until both were ready. The authors found no evidence for parallel processing and no evidence that the management of central processing of dual tasks is qualitatively different in older adults than it is in younger adults. When one response was verbal and the other manual, the 2 responses closely coincided. When both responses were manual, the authors did find that the first response was not delayed enough to coincide with the 2nd and that this underestimation was greater in older adults. Reprinted by permission of the publisher.